2016
DOI: 10.1021/jacs.6b08175
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Electron–Phonon Coupling and Slow Vibrational Relaxation in Organic–Inorganic Hybrid Perovskites

Abstract: Quantum and dielectric confinement effects in 2D hybrid perovskites create excitons with a binding energy exceeding 150 meV. We exploit the large exciton binding energy to study exciton and carrier dynamics as well as electron-phonon coupling in hybrid perovskites using absorption and photoluminescence (PL) spectroscopies. At temperatures below 75 K, we resolve splitting of the excitonic absorption and PL into multiple regularly-spaced resonances every 40-46 meV, consistent with electron-phonon coupling to pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
393
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(434 citation statements)
references
References 41 publications
38
393
3
Order By: Relevance
“…99.7% of the excitonic photoluminescence (PL) is emitted out of the lowest-lying excited state at 15 K. However, 0.3% of the PL is emitted out of discrete higher energy resonances that also appear at similar energies in the absorption spectrum, each separated by ~40 meV from the lowest-lying resonance and from one another. 5 The existence of hot PL violates Kasha's rule, which states carriers relax to the lowest-lying excited state before fluorescing. 7 PL from these higher-energy resonances competes with relaxation to the lowestlying excited state, and the kinetics combined with the regular spacing of the resonances led us to hypothesize that we observed a phonon progression.…”
Section: Toc Graphicmentioning
confidence: 99%
“…99.7% of the excitonic photoluminescence (PL) is emitted out of the lowest-lying excited state at 15 K. However, 0.3% of the PL is emitted out of discrete higher energy resonances that also appear at similar energies in the absorption spectrum, each separated by ~40 meV from the lowest-lying resonance and from one another. 5 The existence of hot PL violates Kasha's rule, which states carriers relax to the lowest-lying excited state before fluorescing. 7 PL from these higher-energy resonances competes with relaxation to the lowestlying excited state, and the kinetics combined with the regular spacing of the resonances led us to hypothesize that we observed a phonon progression.…”
Section: Toc Graphicmentioning
confidence: 99%
“…[12,37] It was demonstrated that electron-phonon coupling in (C 4 H 9 NH 3 ) 2 PbI 4 is dominated by homopolar optical phonons through deformation potential, while the contribution from acoustic phonon and longitudinal optical phonons (Fröhlich coupling) are negligible. [12,37] It was demonstrated that electron-phonon coupling in (C 4 H 9 NH 3 ) 2 PbI 4 is dominated by homopolar optical phonons through deformation potential, while the contribution from acoustic phonon and longitudinal optical phonons (Fröhlich coupling) are negligible.…”
Section: Doi: 101002/adom201700373mentioning
confidence: 99%
“…Thesame decay behaviors also confirm the absence of Auger combination process at the present experiment condition. We ascribe the first ultrafast component to the cooling of the hot STE states, [28][29][30][31] identified by the blue shifting of the excited state absorption of (C 8 NH 12 ) 4 BiBr 7 ·H 2 Oa ts hort decay times ( Figure S10d). It is notable that the STE absorption of (C 8 NH 12 ) 4 Bi 0.57 Sb 0.43 Br 7 ·H 2 Oi sm uch broader than that of (C 8 NH 12 ) 4 BiBr 7 ·H 2 O, indicating new STEs are generated.…”
mentioning
confidence: 94%